2022
DOI: 10.3389/fnut.2022.885497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Sources of Calcium in the Diet on Growth Performance, Blood Metabolic Parameters, and Intestinal Bacterial Community and Function of Weaned Piglets

Abstract: Despite a well-documented effect of calcium on the piglet's intestinal microbiota composition, it is less known about changes in microbial function or the effect of different sources of calcium. The experiment was designed to study the effects of dietary calcium from different sources on production, immune indexes, antioxidant capacity, serum biochemical indexes, and intestinal microflora of weaning piglets. A total of 1,000 piglets were randomly assigned to five groups (10 replicate pens per treatment with 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this study, it was found that piglet dietary supplementation of macleaya extract and glucose oxidase combination resulted in significant increase in the abundance of Firmicutes bacteria. Previous studies have shown that increasing the richness of Firmicutes in the cecum could increase the production of short-chain fatty acids, which can reduce the intestinal pH value and inhibit harmful bacteria growth (41)(42)(43). The combination of MCE and GOD can improve the composition of the cecal microbiota, thereby promote intestinal health in piglets.…”
Section: Figurementioning
confidence: 99%
“…In this study, it was found that piglet dietary supplementation of macleaya extract and glucose oxidase combination resulted in significant increase in the abundance of Firmicutes bacteria. Previous studies have shown that increasing the richness of Firmicutes in the cecum could increase the production of short-chain fatty acids, which can reduce the intestinal pH value and inhibit harmful bacteria growth (41)(42)(43). The combination of MCE and GOD can improve the composition of the cecal microbiota, thereby promote intestinal health in piglets.…”
Section: Figurementioning
confidence: 99%